Heritage clay brick characterization and assessment with compatible contemporary bricks for retrofitting of heritage monuments - Guljit Singh,; Varinder Singh Kanwar,; Anshu Tomar, (Vietnam Journal of Science and Technology, 2024)
Various mughal architecture clay brick masonry monuments were built in the Punjab state of northern India from the late 14th to late 19th centuries. Nanakshahi monuments (era of 1st Sikh Guru-Guru Nanak Dev Ji) are gigantic clay brick masonry structures constructed of lime and lime surkhi mortar (a powdered form of red burnt clay brick). Currently, this study is focused on identifying a suitable material for repairing and strengthening heritage clay brick monuments. Using the mineralogical composition of heritage Nanakshahi clay bricks (NSCB), the study compares them with contemporary clay bricks (CCB) from the same region, and then compares them to newly prepared clay bricks (NPCB), which have similar composition and dimensions to NSCB. The X-ray fluorescence confirms that the NSCB samples of southeast Punjab have an elemental composition consisting of filler SiO2 and binding elements like Al2O3, Fe2O3, CaO, K2O and MgO. The average density of ancient NSCB and CCB has been found to be similar; the ancient NSCB has a lower water absorption rate and porosity in contrast to the present-day clay bricks. The Initial rate of absorption  of an ancient NSCB is quite higher. In comparison to the heritage NSCB, the CCB's compressive strength value is lower and uniaxial compression strength of newly prepared clay bricks (NPCB) of similar mineralogical composition and dimensions is comparable to that of the heritage NSCB from Punjab districts. The significance of the study is to suggest a compatible material for strengthening of heritage clay brick monuments of northern India.